2005
DOI: 10.1158/0008-5472.can-04-3208
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Modeling of Human Pancreatic Duct Epithelial Cell Transformation Defines Gene Expression Changes Induced by K-ras Oncogenic Activation in Pancreatic Carcinogenesis

Abstract: Genetic analysis of pancreatic ductal adenocarcinomas and their putative precursor lesions, pancreatic intraepithelial neoplasias (PanIN), has shown a multistep molecular paradigm for duct cell carcinogenesis. Mutational activation or inactivation of the K-ras, p16INK4A , Smad4, and p53 genes occur at progressive and high frequencies in these lesions. Oncogenic activation of the K-ras gene occurs in >90% of pancreatic ductal carcinoma and is found early in the PanINcarcinoma sequence, but its functional roles … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 40 publications
(40 reference statements)
7
111
1
Order By: Relevance
“…2B). Our results differ with a recent study that found that activated K-Ras did not alter the anchorage-dependent growth properties of immortalized pancreatic ductal epithelial cells (26).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…2B). Our results differ with a recent study that found that activated K-Ras did not alter the anchorage-dependent growth properties of immortalized pancreatic ductal epithelial cells (26).…”
Section: Resultscontrasting
confidence: 99%
“…To date, several pancreatic cell systems have been described to study Ras oncogenesis (21)(22)(23)(24)(25)(26). Although Lohr et al (22) generated immortalized cells expressing SV40 large T antigen and mutant K-Ras that formed contact-independent colonies in vitro and orthotopic tumors in mice, these were of bovine and not human origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interplay is based on three basic processes: production of autocrine and paracrine factors, cell-matrix contact, and signaling by direct cell-cell interactions (39,40). To establish cell culture models for the study of the tumorigenesis of human pancreatic cancer in vitro, we have developed immortalized cultures of HPDE cells derived from normal epithelium (41). The aim of these studies was to investigate the immortalization-transformation sequence of these cells to understand better the implication of various mutations, including the role of paracrine factors such as KGF/FGF-7, a potent mitogenic paracrine mediator of epithelial cells, in the development of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, they have limited genetic aberrations, grow in an anchorage-dependent manner, and are non-tumorigenic in mice [8]. Further, stable expression of oncogenic Ki-Ras G12V caused transformation of HPDEE6E7 cells and activated signaling molecules implicated in human pancreatic cancer development such as the PI3K protein kinase mediator Akt [9].…”
Section: Introductionmentioning
confidence: 99%